Does septum resection improve reproductive outcomes for women with a septate uterus? A systematic review and meta-analysis - Liu, Chang; Liao, Zhiqi; Gong, Xueqi; Chen, Yinwei (Frontiers in Endocrinology, 2024)
Objective: To investigate whether incising the septum facilitates reproductive outcomes for patients with septate uterus compared with expectant management. Methods: Researches were retrieved from three electronic databases PubMed, Embase, and Cochrane Library with no time and language restriction. Two authors selected the articles independently and extracted data regarding study characteristics, quality, and results. A random-effect model was employed, and summary risk ratios (RR) at 95% confidence intervals (CI) were calculated.Results: A total of 468 patients from 2 random controlled trials and 1 cohort study were included in the systematic review and meta-analysis. Pooled results showed that septum resection could not improve the live birth rate for patients with septate uterus (RR=0.84, 95%CI 0.56-1.25, P=0.39). Besides, no significant differences were found between the septum resection and management groups in terms of the clinical pregnancy (RR=1.08, 95%CI 0.81-1.44, P=0.60), abortion (RR=1.99, 95%CI 0.80-4.98, P=0.14), and preterm delivery rates (RR=0.99, 95%CI 0.42-2.31, P=0.98).Our data provide clear evidence that septum resection could not offer any improvements in the reproductive outcomes for patients with septate uterus. These findings might be useful to revise the current guidance.